Hybrid Cloud Security Measures and Research Challenges - et. al., V.Ambica, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud Computing is a cropping technology. There are many researches going under this cloud technology. There are many challenges in terms of security for data stored in cloud. Currently there are four cloud deployment models named as public cloud, private cloud, community cloud and hybrid cloud available in the market. According to the requirements customers can avail one among the four available cloud models. This paper especially discusses the security problems and stinks occurs for hybrid cloud. This paper also analyzes various factors that effects the security of the information stored in cloud. It provides a better understanding of the cloud computing research challenges, open issues and helps to find top security threats and solutions in hybrid cloud.